Immune response and pathophysiological features of Klebsiella pneumoniae in mice - Nasma Maged Elemary; Mohamed Mahrous Emara; Amin Abd Elhady Tahoun; Walied Abdo Sobhy; Ramadan Ahmed Eloomany (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the bacterial colonisation of mice organs and faeces infected with 3 strains of Klebsiella pneumoniae, to measure levels of tumour necrosis factor-alpha, tumour necrosis factor-beta and interleukin-6 in mice serum, and to evaluate immune response of mice infected with Klebsiella pneumoniae. Method: The animal study was conducted at Kafreslsheikh University, Egypt, in 2021, and comprised mice 5-7 weeks old who were infected with 3 strains of Klebsiella pneumoniae; K80uge+ (uri, kfu+, mrkD+; K68 gyrA+(gyrase A), mrkD+; and K84 uge+, kfu+, mrkD+”. They were monitored for 14 days. The bacterial colonisation of mice livers, lungs, spleens and faeces were determined using culture on MacConkey agar. The percentage of neutrophils detected as cluster of differentiation 11b+ and cluster of differentiation 45+ in the mice serum was determined by flow cytometry. Levels of tumour necrosis factor-alpha and tumour necrosis factor-beta were measured using enzyme-linked immunosorbent assay. Results: There were 4 sets of female mice [1 control and 3 infected groups for which 3 K. pneumoniae strains (K80 uge+, kfu+, mrkD+; K68 gyrA+, mrkD+; and K84 “uge+, kfu+, mrkD+)] weighing 13-24gm was used. Colonisation of mice organs and faeces was high after 24 hours then declined rapidly after 3 days, 10 days and 14 days in case of infection with capsulated and non-capsulated strains of bacteria. Livers, lungs and spleens showed maximum inflammation after 24 hours, then declined rapidly. Both cytokine production and organ inflammation increased after one day of infection. There was a significant correlation between the produced cytokines and histopathological changes in liver, lung and spleen. The neutrophils increase in case of infection with K84 and K80 was more than non-capsulated K68. Conclusion: Neutrophils were found to play an important role in the clearance and treatment of Klebsiella pneumoniae. Keywords: Mice, Interleukin, Neutrophils, Spleen, Cytometry, Lung, Inflammation, Liver, Faeces, Enzyme, Immunity.